MATHEMATICAL MODELLING OF HIGH-INTENSITY HEAT FLUX ON THE ELEMENTS OF HEAT-SHIELDING COMPOSITE MATERIALS OF A SPACECRAFT - Pronina, Polina F.; Sun, Ying; Tushavina, Olga V. (Journal of Applied Engineering Science, 2020)
The physical and mathematical foundations of the heat-shielding composite materials (CM) functioning under the conditions of aerogasdynamic heating of hypersonic aircraft, as well as under the conditions of the point effect of high-energy radiation are considered. On the basis of the new laws of CM binding substance decomposition and nonlinear filtration, a complex physical and mathematical model of heat and mass transfer in anisotropic CMs is proposed, taking into account the connections of deformation and temperature fields, suitable for studying most CMs used as heat-shielding elements for modern flying vehicles (FV). A methodology has been developed for the numerical solution of the entire complex problem on the basis of economical absolutely stable numerical methods. Multiple results of numerical simulation of the thermal state of CMs under conditions of their thermal destruction at high temperatures have been obtained.
Keywords: reusable space system; composite materials; pyrolysis gases; temperature field; heat and mass transfer problems